Repeatability and minimum number of bunches for evaluating pataua palm (Oenocarpus bataua) germplasm (Research, Society and Development, 2025)
The Pataua palm (Oenocarpus bataua Mart.) is a perennial food palm tree, widely distributed in the northern states. Its potential lies in its fruits, which are used in beverages, popsicles, ice cream, liqueurs, nectar, jellies and in the extraction of olive oil similar to that of olives. The market is local, supplied by fruits from extractivism, due to the scarcity of information for domestication. The objective was to estimate the repeatability coefficients, determine the predictability and the minimum number of bunches in Pataua palm genotypes for germplasm evaluation. Data were collected from 31 genotypes in full production, kept in the Pataua palm Active Germplasm Bank (BAG Pataua palm), at Embrapa Amazon Eastern, Belém, PA. From each genotype, two successive bunches were collected and six characters evaluated. The repeatability coefficients, determination and the number of measurements required were estimated by three methods in the Genes software. The repeatabilities ranged from 0.14 to 0.80, with the lowest values in the fruit yield per bunch (FYB) and bunch rachis length (BRL), and the highest in the weight of ten fruits (WTF). The coefficients of determination ranged from 24.5% to 88.8%, with WTF being the most accurate. The number of measurements ranged from one (WTF, 0.85) to 116 (FYB, 0.95) bunches. The WTF presented the best predictions at two levels (0.85 and 0.90). Thus, the PDF is indicated as a descriptor for evaluating the germplasm of the species, using one to five bunches, ensuring predictability of up to 95% of the real value.